2007
DOI: 10.1128/jb.01397-06
|View full text |Cite
|
Sign up to set email alerts
|

The lspA Gene, Encoding the Type II Signal Peptidase of Rickettsia typhi : Transcriptional and Functional Analysis

Abstract: Lipoprotein processing by the type II signal peptidase (SPase II) is known to be critical for intracellular growth and virulence for many bacteria, but its role in rickettsiae is unknown. Here, we describe the analysis of lspA, encoding a putative SPase II, an essential component of lipoprotein processing in gram-negative bacteria, from Rickettsia typhi. Alignment of deduced amino acid sequences shows the presence of highly conserved residues and domains that are essential for SPase II activity in lipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…However, the secretion pathway of RT0522 protein into the host cytoplasm, its posttranslocational modification (if any), and the mechanism of interaction with host organelles remain unknown. In silico analysis revealed that the protein RT0522 does not contain a signal peptide sequence, suggesting that this protein is not secreted to the host cell cytoplasm through the Sec-dependent protein secretion pathway of rickettsiae (1,(29)(30)(31). However, other secretory pathways, e.g., the type IV protein secretion pathway, have been identified in rickettsiae (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the secretion pathway of RT0522 protein into the host cytoplasm, its posttranslocational modification (if any), and the mechanism of interaction with host organelles remain unknown. In silico analysis revealed that the protein RT0522 does not contain a signal peptide sequence, suggesting that this protein is not secreted to the host cell cytoplasm through the Sec-dependent protein secretion pathway of rickettsiae (1,(29)(30)(31). However, other secretory pathways, e.g., the type IV protein secretion pathway, have been identified in rickettsiae (9).…”
Section: Discussionmentioning
confidence: 99%
“…The titers of partially purified R. typhi from Vero76 cells were determined using the Live/ Dead BacLight bacterial viability assay (Molecular Probes, Eugene, OR) as previously described (29). A monolayer of Vero76 cells (approximately 1 ϫ 10 6 cells) was infected with R. typhi at a multiplicity of infection of approximately 100 rickettsiae.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work on R. typhi protein secretion has focused mainly on the characterization of the Sec pathway (49)(50)(51) and the rvh T4SS (26,27). Little is known about the function of the rickettsial T1SS, despite the presence of genes encoding the T1SS components within all sequenced Rickettsia genomes.…”
mentioning
confidence: 99%
“…Bacterial SPase II cleaves the signal peptide from glyceride-modified prolipoproteins, while they are translocated across the cytoplasmic membrane (37). It was shown recently that overexpression of R. typhi LspA in E. coli confers resistance to globomycin, a specific inhibitor of SPase II (18), and genetically complements the growth defect of a SPase II-deficient E. coli mutant (38). Although the percentage of amino acid identity between R. typhi LspA and E. chaffeensis LspA is only 36%, five domains and catalytic residues that are considered to be essential for the enzymatic activity of bacterial SPase II (37) are conserved in the LspA proteins of E. chaffeensis and other members of the family Anaplasmataceae (Fig.…”
Section: Resultsmentioning
confidence: 99%